REKOMENDASI PERANGKAT KOMPUTER UNTUK E-COMMERCE DENGAN METODE ANALYTIC HIERARCHY PROCESS - Andre Sutanto (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Computer recommendation application with analytic hierarchy process is a system that provides an recommendation for user who need a computer with capability running a software that the user want. The recommendation obtained from the minimum system requirements, performance and price of each component computer. The system created using analytic hierarchy process  to give an recommendation for user. For the result system will give eight computer that can run the software user want and the computer with best performance / cost point will highlighted.